The Impact of Leader in Me on the School Climate and Student Behaviours: A Meta-Analysis - Villares, Elizabeth; Miller, A. Eve; Chevalier, Jennifer (International Journal of Education Policy and Leadership, 2023)
This meta-analysis investigates the impact of the Leader in Me process on teachers’ perceptions of their school climates and student behaviour. Twelve studies involving 198,176 students resulted in an overall effect size of d = .20. The effect sizes for student climate (d = .34) and student behaviour (d = .16) were determined separately. The results of this meta-analysis connect the Leader in Me intervention with the whole-school implementation model for maintaining a supportive learning environment.